High-altitude UAS pseudo-satellites: architecture for end-to-end military communications - Lyon, Harry M.; Inalhan, Gokhan; Bourne, Daniel; Tsourdos, Antonios (AIAA, 2021)
High-Altitude Pseudo-Satellites (HAPS) have been identified as a potential option to either supplement or replace various military communications services. A network of HAPS aircraft operating at an altitude of 20km offers localized, high performance services to military operations. The intention of this work is to investigate whether a network of HAPS (specifically Airbus’ Zephyr S platform) is preferable to that of standard military communications infrastructure. Individual technologies were not studied directly, but rather the overall services were analyzed. This study will not replace services one-for-one, but rather investigate how HAPS can augment capabilities of current infrastructure. This need for supplementation of services may arise from increased service demand, or in the case of emergency, where other systems may be compromised. A particular emphasis is placed on command and control (C2) of the aircraft, and how this can be harnessed to produce the required communications network.
Keywords: Information Command and Control Systems